Conflict Relapse and the Sustainability of Post-Conflict Peace - Walter, Barbara F. (Washington, DC: World Bank, 2012)
Finds civil wars and their recurrence fall into three patterns: (1) the 'conflict trap,' meaning once a country experiences one civil war, it is significantly more likely to experience additional episodes of violence as shown by a 57 percent recidivism rate from 1945-2009; (2) the dominant form of armed conflict in the world today is recurring civil war; and (3) concentration of civil wars in a few regions, especially in the poorest and weakest states of sub-Saharan Africa. Renewed wars result primarily from factors such as grievances based on economic under-development and ethnic and religious differences, and opportunities for rebellion created by rebel recruitment, money and supplies, and constraints on state capacity. Political institutions are the key to explaining why some countries can escape the conflict trap while others cannot. How the war ends--whether by ceasefire or comprehensive peace treaty--appears not to matter, although the government's ability to credibly commit to a peace agreement likely affects its ability to avoid repeat civil war.